Quality of life regarding the health of people with diabetes mellitus type 2 - Loisláyne Barros Leal; Ionara Holanda Moura; Rumão Batista Nunes de Carvalho; Nahadja Tahaynara Barros Leal; Anael Queirós Silva; Ana Roberta Vilarouca da Silva (Universidade Federal do Ceará, 2014)
The objective of this study was to evaluate the quality of life related to the health of people with diabetes mellitus type 2. It was a cross-sectional research conducted with 100 diabetics. Data collection was conducted during March and April 2012 with two teams of the Family Health Strategy in Picos, PI, Brazil through individual interviews. A form containing socioeconomic, clinical and the Medical Outcomes Study 36 - Item Short Form Health Survey (SF-36). The average among the participants of the SF-36 ranged from 34.8 (physical aspects) to 72.0 (mental health). There was a statistically significant association between pain and functional capacity with sex, as well as functional capacity and emotional aspects with physical activity (p <0.05). It was concluded that the participants had a better quality of life in the assessment in the dimensions that comprise mental components.